Optimization of performance under off-design conditions for dual-pressure organic Rankine cycle with hot source splitting - Shiqi Wang; Zhongyuan Yuan; Kim Tiow Ooi; Xiangyu Chang; Nanyang Yu (Energy Nexus)
The Dual-Pressure Organic Rankine Cycle system, integrated with Hot Source Splitting (DORC-HSS), demonstrates enhanced performance by optimizing heat matching. A primary challenge in deploying the DORC-HSS system lies in its off-design performance, particularly when faced with varying conditions of heat and cold sources. By using the first law of thermodynamics and the logarithmic mean temperature difference method, the MATLAB model of the system is established, and the net output power is optimized by particle swarm optimization. Our analysis reveals that in optimal off-design scenarios, the working fluid exits each loop preheater nearing a saturated liquid state. The increase in hot water flow rate leads to a decrease in the superheat degree in the high-pressure loop. Conversely, the working fluid at the expander inlet in the low-pressure loop consistently maintains a saturated vapor state. Furthermore, a 20.0% increase in optimal output power is observed for every 5 °C rise in hot water inlet temperature, and a 12.2% increase for every 20 kg/s increment in hot water flow rate. The highest thermal and exergy efficiencies achieved are 8.54% and 49.98%, respectively. A reduction of 1 °C in cooling water temperature corresponds to a 3.5% increase in output power. When the cooling water inlet temperature is 17 °C, the highest thermal and exergy efficiencies are 8.0% and 52.3%. The optimal hot water split ratio ranges from 67% to 79%. This optimization method can be used for any waste heat recovery system using DORC-HSS. Industries can approach control targets, ensuring the safe operation and translating into meaningful energy savings and lower operating costs. The economic benefits from such enhancements could shorten the payback period for DORC-HSS installations.